2007
DOI: 10.1111/j.1467-8624.2007.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and the Body Mass Index and Overweight Status of Children and Adolescents

Abstract: Associations between sleep and the body mass index (BMI) and overweight status of children and adolescents were estimated using longitudinal data from a nationally representative sample of 2,281 children aged 3-12 years at baseline. Controlling for baseline BMI, children who slept less, went to bed later, or got up earlier at the time of the first assessment had higher BMIs 5 years later and were more likely to be overweight. Child age moderated the relationship between bedtime and BMI. In addition, the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
272
6
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(300 citation statements)
references
References 34 publications
19
272
6
3
Order By: Relevance
“…[17][18][19][20][21] However, none of these studies investigated whether changes in BMI are associated with changes in sleep duration or studied this relationship during the crucial period of puberty in which sleep duration diverges. We showed, using univariate analysis of variance, that with progressive Tanner stages, BMI increases and sleep duration decreases in an interrelated way, independent of the baseline BMI at start of puberty, FTO allele genotype (rs9939609), BMI of the father and mother, as well as changes during the progressive Tanner stages in Baecke scores and hours television viewing (R 2 ¼ 0.38, Po0.02).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20][21] However, none of these studies investigated whether changes in BMI are associated with changes in sleep duration or studied this relationship during the crucial period of puberty in which sleep duration diverges. We showed, using univariate analysis of variance, that with progressive Tanner stages, BMI increases and sleep duration decreases in an interrelated way, independent of the baseline BMI at start of puberty, FTO allele genotype (rs9939609), BMI of the father and mother, as well as changes during the progressive Tanner stages in Baecke scores and hours television viewing (R 2 ¼ 0.38, Po0.02).…”
Section: Discussionmentioning
confidence: 99%
“…From this observed relationship cause and effect cannot be disentangled. A larger increase in BMI following a larger reduction in sleep duration might be plausible, based on the longitudinal study from Snell et al 18 that showed a relationship between sleep duration measured at the first time point and BMI measured after a 5-year interval, and not vice versa. On the other hand, if sleep duration were to be reduced following an increase in BMI, a plausible theory would be sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short sleep duration in children has been associated with higher body mass index (BMI) 5 y after baseline (15). In addition, children with short sleep durations had significantly higher BMIs at 32 y of age, compared with the adult BMIs of children with moderate and long sleep durations (16).…”
mentioning
confidence: 98%
“…to provide a representative picture regarding the complexity of documenting sleep duration in children, a synopsis of several scientific papers on the sleep-weight debate from 1990 onward was tabulated (table 1 [10][11][12][13][14][15][16][17][18][19][20][21] ). even to the naked eye, it becomes readily apparent that although these studies are methodologically heterogeneous, the reported associations require further investigation.…”
Section: The Conglomerate Of Multifactorial Components Potentially Comentioning
confidence: 99%